(untitled) (Journal of the College of Languages (JCL), 2025)
It is Surprising that speech feature does not stop even with silence, whether this silence is a disable of the speech device or illness which makes man unable to speak ; and stranger than this, that man does not stop talking even while sleeping in dreams and the analects within even though , they are mostly silent. So, it becomes inevitable to offer a linguistic theme calls to communicate, as long as there are people communicating. Because novel is another vision of life, it is necessary to bring out people, so you give the communication its meaning particularly reading communication, and all its claims of open interpretations presented by the character , declared or hidden, so, the reader would receive these interpretations to think about consequences The character is a carrier vessel, which connects both ends of the novel, the hidden party, the writer and the visible party , the reader, the two parties connect both ends of the novel and its emotions even though there is no description of physical or virtual of decorations and accessories and thus the character becomes the touchstone in the processes of writing and reading together. In modern writing , we may encounter characters that take a stagnation setting and during narration process , it becomes just a repletion to itself, imprison of the soul within the body , rumination and rerepresntation of the past by recalling mythological figures to help him cling to life. I have addressed the mentioned above in many levels , such as relationship between names and characters (heritage, both legendary and religiously) historical figures, as well analyzing character Herrmonoutikie. It is necessary for the reader to understand the character in novels in order to be able to communicate with them or help him to participate , along with the help of characters , in making other understand. Novel is a new way to understand life. The last level is the motion impact of the text , which plays a major role in transferring events from place to another even though it is an intertextuality the author trying to establish the novel, even if it exceeds the sanctity of some of the texts, as it comes to cynicize religious figures, to divert the stable concepts. And finally the results that summarize of the study along with most important notes